Stages Of Development of Cloud Technology in Education - Shukurov Akmal Uktamovich (Genius Publishing Group, 2022)
It is necessary to take into account the opportunities of the students without neglecting their personal e-learning environment. Education system based on cloud technology
Keywords: Electronic textbooks; e-learning, education; method; information